P125 Role of UCEIS vs. MES in predicting patients unresponsive to biological therapy and need for surgery: a retrospective single-centre analysis. (25th January 2019) - Variola, A; Di Ruscio, M; Barugola, G; Lunardi, G; Massella, A; Bocus, P; Geccherle, A
Abstract: Background: Biological drugs represent the best choice for treating patients with moderate to severe ulcerative colitis (UC). About 60% of patients fail to achieve clinical and endoscopic remission and about 20% undergo colectomy. The ulcerative colitis Endoscopic Index of Severity (UCEIS) is a new validated score but the Mayo Endoscopic Subscore (MES) still represents the most used index. The aim of this study was to evaluate the predictive role of UCEIS and MES in identifying patients not responding to biological therapy and their need for surgery. Methods: We retrospectively evaluated patients enrolled between 2014 and 2018. Endoscopic disease activity was assessed with MES and UCEIS at baseline and at Week 48. Unresponsiveness was defined as UCEIS ≥ 2. Statistical analysis included Fisher exact test, receiver-operator characteristic (ROC) curves and log-rank test for Kaplan–Meier plots. A p -value of <0.05 was considered significant. Results: Sixty-one patients were included (28 infliximab, 10 adalimumab, 20 golimumab, 3 vedolizumab). Forty-three patients (70.5%) were unresponsive to therapy. The UCEIS, unlike the MES, was found to be significantly associated with unresponsiveness ( p = 0.003 vs. p = 0.389). The area under the ROC curves (AUROC) of UCEIS were 0.58, 0.69 and 0.60, using cut-off value of 7, 6 and 5. Specificity was 94% and sensitivity was 44% using cut-off value of 6. The AUROC of MES was 0.57 with specificity and sensitivity of 50% and 65%, respectively, using a cut-off value of 3. Among unresponsive patients, 13 (30.2%) underwent colectomy for treatment failure. Twelve (92.3%) patients were MES = 3 at baseline with an overall colectomy-free survival rate significantly lower compared with MES = 2 ( p = 0.007). According to the UCEIS at baseline, 6 patients (46.2%) with UCEIS 5-6 and 7 (53.8%) with UCEIS ≥ 7 needed for surgery. When the UCEIS ≥ 7, 100% of patients underwent colectomy (log-rank test for UCEIS p < 0.001). Colectomy-free survival rates according to the UCEIS score (all patients with MES = 3 at baseline). ROC curves of UCEIS (cut-off value of 6) vs. MES (cut-off value of 3) in predicting response to treatment. Conclusions: The UCEIS score, compared with MES, better predict UC patients unresponsive to biological therapy. It is also useful for identifying patients needing colectomy.